The Character Building of Discipline in Learning PKn at Sma Negeri 2 Tondano - Telly D. Wua,; Sjamsi Pasandaran,; Benedikta F. Lalogiroth, (Technium Social Sciences Journal, 2023)
The main purpose of this exploration is to find out how the Civics training experience is and the factors that influence student discipline progress at SMA Negeri 2 Tondano. The technique used in this study is an interesting abstract approach. The results showed that Civics learning practices were carried out by teachers in managing the character of student discipline at SMA Negeri 2 Tondano, namely: arousing student enthusiasm, equipping students with an understanding of good disciplinary behavior, using fun learning media such as the quizizz application so that students are more stable and dynamic in participating in Civics learning. Variables that influence Civics learning practices in forming students with controlled character at SMA Negeri 2 Tondano are self elements which include insights, considerations and perspectives, peer factors, family elements to choose good learning methods.